2020
DOI: 10.1055/s-0040-1710355
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Magnetic Resonance Imaging of Cortical and Trabecular Bone

Abstract: Bone is a composite material consisting of mineral, organic matrix, and water. Water in bone can be categorized as bound water (BW), which is bound to bone mineral and organic matrix, or as pore water (PW), which resides in Haversian canals as well as in lacunae and canaliculi. Bone is generally classified into two types: cortical bone and trabecular bone. Cortical bone is much denser than trabecular bone that is surrounded by marrow and fat. Magnetic resonance (MR) imaging has been increasingly used for nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 158 publications
(253 reference statements)
0
11
0
Order By: Relevance
“…NMR spectroscopy and MRI represent the primary methods used to nondestructively study bone hydration ( Jerban et al, 2020c ; Mroue et al, 2015 ; Singh et al, 2013 ). Compelling progress in solid-state NMR (ssNMR) has allowed us to study the direct relationship of bound water to a host of extracellular matrix components.…”
Section: Imaging and Spectral Methods To Quantify Bone Watermentioning
confidence: 99%
“…NMR spectroscopy and MRI represent the primary methods used to nondestructively study bone hydration ( Jerban et al, 2020c ; Mroue et al, 2015 ; Singh et al, 2013 ). Compelling progress in solid-state NMR (ssNMR) has allowed us to study the direct relationship of bound water to a host of extracellular matrix components.…”
Section: Imaging and Spectral Methods To Quantify Bone Watermentioning
confidence: 99%
“…For example, Wurnig et al proposed to use the SPIR-UTE sequence to image trabecular bone 31 and reported a T2* of 2.42 AE 0.56 msec at 3 T, which is much longer than the T2* of 0.31 AE 0.01 msec for trabecular bone measured with STAIR-UTE, 28 or a T2* of $0.3 msec for cortical bone measured with various IR-based UTE techniques. [32][33][34] The much longer T2* suggests that SPIR-UTE imaging of trabecular bone is subject to significant fat signal contamination. Meanwhile, the STAIR-UTE-measured T2* values for trabecular bone are very close to the IR-UTE-measured T2* values for cortical bone, which suggests that marrow fat is nearly completely suppressed, with signals from trabeculae being selectively detected in STAIR-UTE imaging.…”
Section: Short Tr Adiabatic Inversion Recovery Utementioning
confidence: 99%
“…The residual fat signal can be much higher than that from trabecular bone. For example, Wurnig et al proposed to use the SPIR‐UTE sequence to image trabecular bone 31 and reported a T2* of 2.42 ± 0.56 msec at 3 T, which is much longer than the T2* of 0.31 ± 0.01 msec for trabecular bone measured with STAIR‐UTE, 28 or a T2* of ~0.3 msec for cortical bone measured with various IR‐based UTE techniques 32–34 . The much longer T2* suggests that SPIR‐UTE imaging of trabecular bone is subject to significant fat signal contamination.…”
Section: Part I: Morphological Ute Imagingmentioning
confidence: 99%
“…Notably, T2* of bone is on the order of hundreds of microseconds, while the echo times (TEs) in conventional clinical MRI sequences are typically several milliseconds or longer ( 11 , 17 ). On the other hand, ultrashort echo time (UTE) MRI sequences have TEs on the order of several to tens of microseconds, which are short enough to detect signal from cortical bone directly and consequently enable quantitative assessment of cortical bone ( 7 9 , 11 , 12 , 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%